2011
DOI: 10.1063/1.3608155
|View full text |Cite
|
Sign up to set email alerts
|

Optimal signal-to-noise ratio for silicon nanowire biochemical sensors

Abstract: The signal-to-noise ratio (SNR) for silicon nanowire field-effect transistors operated in an electrolyte environment is an essential figure-of-merit to characterize and compare the detection limit of such devices when used in an exposed channel configuration as biochemical sensors. We employ low frequency noise measurements to determine the regime for optimal SNR. We find that SNR is not significantly affected by the electrolyte concentration, composition, or pH, leading us to conclude that the major contribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
101
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(106 citation statements)
references
References 19 publications
(18 reference statements)
4
101
1
Order By: Relevance
“…[18] This low-frequency 1/f noise is even more pronounced for devices that are scaled down to nanometer dimensions, where the channel current becomes more prone to fluctuations due to, particularly, interface and surface trap states. [63,64] It is the level of these unwanted fluctuations (along with the sensing response S) that determines the ultimate detection limit of GFET biosensors. The 1/f noise of graphene monolayers supported on a substrate is comparable to that of bulk semiconductors (including Si).…”
Section: Electrical Noise Performances Of Graphene Materialsmentioning
confidence: 99%
“…[18] This low-frequency 1/f noise is even more pronounced for devices that are scaled down to nanometer dimensions, where the channel current becomes more prone to fluctuations due to, particularly, interface and surface trap states. [63,64] It is the level of these unwanted fluctuations (along with the sensing response S) that determines the ultimate detection limit of GFET biosensors. The 1/f noise of graphene monolayers supported on a substrate is comparable to that of bulk semiconductors (including Si).…”
Section: Electrical Noise Performances Of Graphene Materialsmentioning
confidence: 99%
“…Currently, two main concepts are considered for optimization of sensitivity: using the subthreshold mode 25 or above-threshold mode 24 .…”
mentioning
confidence: 99%
“…It was recently demonstrated that the low-frequency noise originating from charge trapping/detrapping at the Si/SiO 2 interface is the prevailing noise source in wet environments, as the noise-level dependency on ion concentration and pH level is negligible. [31][32][33] This EFN degree of freedom improves the signal-to-noise ratio, which is crucial for biosensing applications because the signal-to-noise ratio level will determine the sensitivity limit of the biosensor. 34 Moreover, the ability to control the vertical position of the channel compromises between the need for maximum proximity of the biological events to the conducting channel on the one hand, and the need for high signal-tonoise ratio on the other.…”
Section: Introductionmentioning
confidence: 99%